THE EFFECT OF PARENTAL COMMUNICATION ON THE GROWTH AND DEVELOPMENT OF MINORS - Dodi Rusmana (SEAN Institute, 2021)
This study aims to determine the effect of parental communication on children's growth and development. This study uses a qualitative approach. Determination of informants in this study using purposive sampling, which determines the informants as the people who know best, the sources in this study are 6 residents of Tegallega Village, Lembursitu District, Lembursitu Village, Sukabumi City. Data collection techniques using online interviews. Based on the results, it can be seen that from the data that can be interpreted, family communication is very important for children's growth and development, from observations and interviews there are still parents who even have difficulty knowing their children's daily lives and controlling their children because they are busy working and only have little time to spend together